†Rudolf Grewe and Constance B. Hieatt, eds.: Libellus de arte coquinaria: An Early Northern Cookery Book - Jaine, Tom (Petits Propos Culinaires, 2024)
†Rudolf Grewe and Constance B. Hieatt, eds.: Libellus de arte coquinaria: An Early Northern Cookery Book: Arizona Center for Medieval and Renaissance Studies, 2001: ISBN 0-86698-264-7: 158 pp., full bibliography and indexes, h/b, 22, £19.